The Cancer Prevention and Control Research Network - Jeffrey R. Harris, MD, MPH, MBA; Pamela K. Brown, MPA; Steven Coughlin, PhD; Maria E. Fernandez, PhD; James R. Hebert, ScD; Jon Kerner, PhD; Marianne Prout, MD, MPH; Randy Schwartz, MSPH; Eduardo J. Simoes, MD, MSc, MPH; Carol White, MPH; Katherine Wilson, PhD (Centers for Disease Control and Prevention, 2005)
The Cancer Prevention and Control Research Network is a national network recently established to focus on developing new interventions and disseminating and translating proven interventions into practice to reduce cancer burden and disparities, especially among minority and medically underserved populations. Jointly funded by the Centers for Disease Control and Prevention and the National Cancer Institute, the Cancer Prevention and Control Research Network consists of sites administered through Prevention Research Centers funded by the Centers for Disease Control and Prevention. The five sites are located in Kentucky, Massachusetts, South Carolina, Texas, Washington State, and West Virginia. The Cancer Prevention and Control Research Networks intervention areas include primary prevention of cancer through healthy eating, physical activity, sun avoidance, tobacco control, and early detection of cancer through screening. The Cancer Prevention and Control Research Network uses the methods of community-based participatory research and seeks to build on the cancer-relevant systematic reviews of the Guide to Community Preventive Services. Initial foci for the Cancer Prevention and Control Research Networks research work groups include projects to increase screening for breast, cervical, and colorectal cancers; to promote informed decision making for prostate cancer screening; and to validate educational materials developed for low-literacy populations.